Agricultural Input Subsidies in Pakistan: Nature and Impact (The Pakistan Development Review, 1995)
Pakistan has a history of subsidising agricultural inputs. Although none of the agricultural inputs were subsidised during the early 1950s, the process was initiated in the second half of the decade by subsidising chemical fertilisers in order to popularise their use [Niaz (1984)]. The list of subsidised inputs and the rate structure of the subsidies were expanded considerably throughout the Sixties. Towards the end of the Sixties, it was noted that almost all the agricultural inputs including fertilisers, insecticides, seeds, irrigation water, tubewell installations, and the operation and purchase of tractors and tractor-related equipment were subsidised in one form or another [Aresvik (1967) and Kuhnen (1989)]. In the 1970s, some curtailment of subsidies occurred as a result of input price increases which followed the worldwide recession, a major oil shock, the credit crunch, the war with India, and the consequent steep devaluation of Pakistani Rupee [Chaudhry (1982)]. Although the subsidies had survived the onslaught of the Seventies and tended to persist on most inputs, the government became totally committed to their removal beginning with the 1980s, under pressures from the IMF and the World Bank [Government of Pakistan (1980)]. As a consequence, there was a total withdrawal of subsidy from seeds, insecticides, tubewells, and tractors. A phased-out withdrawal of fertiliser subsidy, culminating in 1984-85 in the case of nitrogenous fertilisers and in 1989-90 in the case of phosphatic and potash fertilisers, was also to be undertaken [World Bank (1986)].